2022
DOI: 10.1007/s13300-022-01272-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Treatment Patterns of Patients with Type 2 Diabetes Mellitus in the Middle East and Africa Cohort of the DISCOVER Study Program: a Prospective Study

Abstract: Introduction Despite the high prevalence of type 2 diabetes (T2D) and suboptimal glycemic control in the Middle East and Africa, comprehensive data on the management of T2D remain scarce. The main aim of this study is to describe the characteristics and treatment of patients with T2D initiating second-line glucose-lowering therapy in these regions. Methods DISCOVER is a global, 3-year, prospective observational study of patients with T2D enrolled at initiation of second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Managing T2DM in the Middle East has shown significant regional variations recently, probably caused by various modifiable factors such as the health system, doctor behavior, and patient compliance. [ 40 ] To achieve the best results, Saudi Arabia should consider and handle each of these to prevent upcoming diabetes in the nation.…”
Section: Discussionmentioning
confidence: 99%
“…Managing T2DM in the Middle East has shown significant regional variations recently, probably caused by various modifiable factors such as the health system, doctor behavior, and patient compliance. [ 40 ] To achieve the best results, Saudi Arabia should consider and handle each of these to prevent upcoming diabetes in the nation.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that they were less frequently prescribed to Italians could be counterbalanced by a more frequent use of SGLT-2 inhibitors, possibly because Italian patients had a greater prevalence of CV diseases and these medications are now recommended even as first-line therapy in this case [16,18]. Interestingly, sulfonylureas and DPP-4 inhibitors were the most prescribed second-line antidiabetic medications in some populations of the DIS-COVER study [20]. GLP-1 analogues could be found only in the group of Italian patients.…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is a great focus on treatments with the potential to prevent HF in patients with diabetes. Regional observational studies such as DISCOVER ME 70 and PACT MEA 71 have shown that glucose‐lowering agents such as sulfonylureas, thiazolidinediones and insulin are often used in the MENAT region. However, these therapies are associated with adverse cardiovascular outcomes, such as an increased risk of incident HF and an increase in mortality and hospitalizations associated with HF 69,72 …”
Section: Introductionmentioning
confidence: 99%